Answer:
?????????????????????????
Answer:
See answer below
Step-by-step explanation:
For the first expression
3 x (x - 2) + 2 = 3 x^2 - 6 x + 2
evaluated at x= 4 we get: 26
and for x = 5 we get 47.
For the second expression
2 x^2 + 3 x - 18
we get the exact same values when doing the evaluation at these two points.
Based on those results, one may think the expressions may be equivalent, but they are not equivalent. Because at any other x-value, their results are different. See for example that for x = 0 the first one gives "2" while the second one gives -18.
Answer:
n=3
Step-by-step explanation:
Hope this helps
Answer:
692914.56
Step-by-step explanation:
(9.2 x 102)
= 938.4
(7.1 x 104)
= 738.4
938.4 x 738.4
=
692914.56
10 4 , so basically you cross multiply : 10x=20 .... 20 divided by 10 is 2 . x=2
___ = ___
5 x